Correcting the "Correctional" Component of the Corrections Officer Role: How Offender Custodians Can Contribute to Rehabilitation and Reintegration. Issue 1 (2nd January 2018) - Schaefer, Lacey
ABSTRACT: Research demonstrates that for many individuals imprisonment fails to rehabilitate or deter, and may actually promote recidivism. What can be done to limit reoffending and improve reentry experiences? One malleable component of custodial corrections is the role of the corrections officer. Alterations in the practices of detention workers may significantly contribute to positive offender outcomes. Drawing from several disparate literatures, this article proposes ten recommendations for how to reform the role of corrections officers in ways that promote rehabilitation and reintegration. Discussed are ways in which corrections officers should emphasize correction, use cognitive behavioral techniques, embody other roles (crisis counsellors, health advocates, corrections counselors, and life coaches), encourage identity substitutions, suggest new routine activities, solicit crime controllers, and facilitate transitions.